An apparatus to study compression stress in fruits and vegetables - da Silva, José Luiz O.; Calbo, Adonai Gimenez (Pesquisa Agropecuaria Brasileira, 1992)
An adjustable and continuous multiple force applicator was developed, to study compression stress related to the transporte and storage of fruits and vegetables, using a cylinder-embolus system of a 10 ml syringe, a two-stage pressure controlling valve, air distributor device and a compressed air tank. The equipment is a modular one with 12 force applicator units (regularly spaced of 8.5 cm) connected to the pressure regulator through the air distributor. To apply the compression force, a 3,35 cm (od) acrylic ring was glued to the embolus. The test of the equipment showed an excellent correlation (R2- = .9996) between the adjusted pressure and the applied force. During a real case study, mature-green ’Kada’ tomato fruits were stored at a temperature of 20 ± 3oC under forces of 0, 2.25, 4.50 and 9.21 N that caused increasing levels of deformation, delayed the color development and reduced the CO2 evolution as a function of the compression force, differently from what happens in the case of impact and vibration stresses.